Occupational Community-Acquired Pneumonia in a Fitter-Splicer with a Significant Smoking History: A Case Report and Expanded Review of the Literature - Anthony Suranta Surbakti; Agus Juanda (International Medical Journal Corp. Ltd, 2025)
Introduction: Community-acquired pneumonia (CAP) is a primary driver of global morbidity and mortality, with its incidence heavily influenced by host and environmental factors. While the roles of age, comorbidities, and smoking are well-established, the contribution of occupational exposures—particularly the complex and synergistic hazards faced by industrial workers—remains a critical and often under-appreciated component of risk assessment. This report presents an in-depth analysis of a fitter-splicer, a profession with a unique combination of respiratory hazards, who developed CAP, providing a platform to explore the intricate relationship between workplace environment, lifestyle factors, and infectious disease susceptibility. Case Illustration: A 50-year-old male with a 30-pack-year smoking history presented with a one-week history of a worsening productive cough, persistent fever, right-sided pleuritic chest pain, and a significant episode of hemoptysis. Physical examination revealed focal findings over the right lower lung, including decreased tactile fremitus, diminished breath sounds, and localized rhonchi, indicative of parenchymal consolidation. Laboratory investigations showed marked neutrophilic leukocytosis and a profoundly elevated C-reactive protein level (165 mg/L). A chest radiograph confirmed dense consolidation in the right lower lobe, consistent with lobar pneumonia. Despite being stratified as low severity by both the CURB-65 and Pneumonia Severity Index (PSI) scores, he was hospitalized due to his clinical presentation and occupational context. He was managed with a dual antibiotic regimen of intravenous ceftriaxone and oral levofloxacin. The patient demonstrated a favorable clinical response and was discharged after a nine-day hospital stay. Discussion: This case serves as a paradigm for the critical interplay between a patient's multifaceted occupational exposures and his extensive smoking history. The role of a